2019
DOI: 10.1002/adfm.201908337
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Dynamics of Hybrid Metal Halide Perovskite Formation via Multimodal In Situ Probes

Abstract: The exploration of the synthetic space of halide perovskites hinges on an enormous number of parameters requiring time-consuming experimentation to decouple and optimize. Here, the formation of the prototype material CH 3 NH 3 PbI 3 (MAPbI 3 ) is investigated at different time and length scales using multimodal in situ measurements to monitor the evolution of crystalline phases, morphology, and photoluminescence as a function of the lead precursors. Kinetically fast formation of crystalline precursor phases al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 68 publications
(84 reference statements)
9
89
0
Order By: Relevance
“…33,34 Co-presence of PbI 2 (diffraction peak ~12.7º) and intermediate orthorhombic phase (MA) 2 (DMF) 2 Pb 3 I 8 was observed when the antisolvent was dripped late, as well as in the film without antisolvent. 19,35 In a previous study we performed in situ diffraction and optical microscope measurements during the synthesis of MAPbI 3 and confirmed the formation of the intermediate (MA) 2 (DMF) 2 Pb 3 I 8 phase together with the needle-like morphology. 35 In addition, enabled by a fully remotely controlled spin coater in the synchrotron hutch, we found that this phase does not require thermal activation but forms already during spin coating and converts into the perovskite phase after about 15s of annealing.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…33,34 Co-presence of PbI 2 (diffraction peak ~12.7º) and intermediate orthorhombic phase (MA) 2 (DMF) 2 Pb 3 I 8 was observed when the antisolvent was dripped late, as well as in the film without antisolvent. 19,35 In a previous study we performed in situ diffraction and optical microscope measurements during the synthesis of MAPbI 3 and confirmed the formation of the intermediate (MA) 2 (DMF) 2 Pb 3 I 8 phase together with the needle-like morphology. 35 In addition, enabled by a fully remotely controlled spin coater in the synchrotron hutch, we found that this phase does not require thermal activation but forms already during spin coating and converts into the perovskite phase after about 15s of annealing.…”
Section: Resultsmentioning
confidence: 58%
“…19,35 In a previous study we performed in situ diffraction and optical microscope measurements during the synthesis of MAPbI 3 and confirmed the formation of the intermediate (MA) 2 (DMF) 2 Pb 3 I 8 phase together with the needle-like morphology. 35 In addition, enabled by a fully remotely controlled spin coater in the synchrotron hutch, we found that this phase does not require thermal activation but forms already during spin coating and converts into the perovskite phase after about 15s of annealing. 35 Thus, if the antisolvent is dripped late (or in the absence of an antisolvent) PbI 2 -MAI-DMF 36 (N,N-dimethylformamide) complex formation happens which templates the final film structure into a non-compact, needlelike morphology.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…As an example, in situ synchrotron diffraction measurements can provide valuable insights and unveil precursor transformation kinetics and secondary phase evolution. 164 The independent control of nucleation and growth during processing of ABX 3 perovskites was identified as a major step towards high quality films including fast initial nucleation to promote uniform coverage but omit microstructural defects. 9 In-depth studies are needed to deconvolve these processes and provide a mechanistic understanding of how nucleation can be promoted and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a few reports have shown that the CH 3 NH 3 PbI 3 thin films fabricated with the addition of PbCl 2 contained slight amount of chloride residues in perovskite grains, which was believed to be responsible for the longer carrier lifetimes [19][20][21][22]. Although the exact role of chloride ion in the growth of perovskite still remains unclear, it has be suggested that chloride ion improves the crystallinity of perovskites, leading to better photophysical properties [13,14,23]. The optical images of the as-grown CH 3 NH 3 PbBr 3 NWs and NPs synthesized with different PbCl 2 /PbAc 2 molar ratios (M) were shown in Fig.…”
mentioning
confidence: 99%